Ответы и объяснения

2012-06-02T10:46:24+04:00

 I способ:

cos^4(x) - sin^4(x) = cos^2(x) - sin^2(x)                  (*)

(cos^2(x)-sin^2(x))*(cos^2(x)+sin^2(x))=cos^2(x) - sin^2(x) 

сокращаем:

cos^2(x)+sin^2(x)=1 

1=1   (ОТТ:  cos^2(x)+sin^2(x)=1)

 Вывод: равенство (*) является тождеством при любом х

 

II способ:

cos^4(x) - sin^4(x) = cos^2(x) - sin^2(x)                  (*) 

 левая часть:  cos^4(x) - sin^4(x) = (cos^2(x)-sin^2(x))*(cos^2(x)+sin^2(x)) = cos^2(x)-sin^2(x).   (ОТТ:  cos^2(x)+sin^2(x)=1)

 cos^2(x)-sin^2(x) = cos^2(x)-sin^2(x) ;

левая часть= правая часть.

   Вывод: равенство (*) является тождеством при любом х